Millennial Generation's Music, Moods, and Impulsive Buying: empirical studies in minimarkets - Putri, Ivon Sandya Sari; Raharso, Sri; Suhaeni, Tintin (Universitas Dian Nuswantoro Semarang, 2021)
The purpose of this paper is to examine the influence of in-store music on impulsive buying among college students (as a millennial generation) in Bandung State Polytechnic, employed customer mood as mediator. Data from 200 respondents were received and analyzed using a regression for testing the hypotheses developed. The results show that the music is significantly affecting the customer's mood and impulsive buying. However, the customer mood does not play significantly affecting impulsive buying. Future research and managerial implications are addressed. Keywords: in-store music, mood, impulsive buying